2021
DOI: 10.3748/wjg.v27.i44.7669
|View full text |Cite
|
Sign up to set email alerts
|

Calycosin attenuates severe acute pancreatitis-associated acute lung injury by curtailing high mobility group box 1 - induced inflammation

Abstract: BACKGROUND Acute lung injury (ALI) is a common and life-threatening complication of severe acute pancreatitis (SAP). There are currently limited effective treatment options for SAP and associated ALI. Calycosin (Cal), a bioactive constituent extracted from the medicinal herb Radix Astragali exhibits potent anti-inflammatory properties, but its effect on SAP and associated ALI has yet to be determined. AIM To identify the roles of Cal in SAP-ALI and the underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In contrast, it was found that the expression of snail, vimentin, and CD31 was increased in the Balb/C nude mice model, suggesting that calycosin may act as an anti‐cancer therapeutic agent by preventing pancreatic cancer cell proliferation 79 . According to an in vivo study conducted on male C57BL/6N mice, calycosin (25–50 mg/kg) blocks HMGB1/NF‐β signaling with decreasing production of pro‐inflammatory cytokines and chemokines, notably TNF‐α, IL‐6, IL‐1, CXCL‐1, and HMGB1 80 . Calycosin (25–200 μM) prevented the growth and viability of pancreatic cancer cells (PaCa‐2, PANC1) by triggering p21Waf1/Cip1‐induced cell cycle arrest at S phase and caspase‐dependent apoptosis via caspase‐3,8,9 activation, elevating Bax expression while lowering Bcl‐2, consequently increasing the ratio of Bcl‐2 to Bax 81 .…”
Section: Evidence Of Anti‐cancer Perspectives Regarding Calycosinmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it was found that the expression of snail, vimentin, and CD31 was increased in the Balb/C nude mice model, suggesting that calycosin may act as an anti‐cancer therapeutic agent by preventing pancreatic cancer cell proliferation 79 . According to an in vivo study conducted on male C57BL/6N mice, calycosin (25–50 mg/kg) blocks HMGB1/NF‐β signaling with decreasing production of pro‐inflammatory cytokines and chemokines, notably TNF‐α, IL‐6, IL‐1, CXCL‐1, and HMGB1 80 . Calycosin (25–200 μM) prevented the growth and viability of pancreatic cancer cells (PaCa‐2, PANC1) by triggering p21Waf1/Cip1‐induced cell cycle arrest at S phase and caspase‐dependent apoptosis via caspase‐3,8,9 activation, elevating Bax expression while lowering Bcl‐2, consequently increasing the ratio of Bcl‐2 to Bax 81 .…”
Section: Evidence Of Anti‐cancer Perspectives Regarding Calycosinmentioning
confidence: 99%
“…79 According to an in vivo study conducted on male C57BL/6N mice, calycosin (25-50 mg/kg) blocks HMGB1/NF-β signaling with decreasing production of pro-inflammatory cytokines and chemokines, notably TNF-α, IL-6, IL-1, CXCL-1, and HMGB1. 80 Calycosin (25-200 μM) prevented the growth and viability of pancreatic cancer cells (PaCa-2, PANC1) by triggering p21Waf1/Cip1-induced cell cycle arrest at S phase and caspase-dependent apoptosis via caspase-3,8,9 activation, elevating Bax expression while lowering Bcl-2, consequently increasing the ratio of Bcl-2 to Bax. 81 Calycosin (100 μM) diminished cyclin A1 and the related cyclin-dependent kinase CDK2 expression while increasing Snail, MMP-2, -9, and p21 gene expression and regulated Raf/MEK/ERK pathway in the pancreatic cell line MIA PaCa-2.…”
Section: Colon Cancermentioning
confidence: 99%
“…Elevated HMGB1 levels in lung tissue and bronchoalveolar lavage fluid (BALF) are demonstrated to be positively correlated with the level of pro-inflammatory cytokines using the PALI mice model. The PALI mice model was established by giving them 4g/kg intraperitoneal injection of L-arginine every hour for 2 hours, and the underlying mechanisms are linked to the activation of the TLR4/MyD88/NF-κB pathway and release of NLRP3 inflammasomes ( 93 96 ).…”
Section: Mechanisms Of Ali Caused By Intestinal Bacterial Dysbiosismentioning
confidence: 99%
“…HMGB1 has been implicated in SAP-induced intestinal barrier injury via the activation of the TLR4/9/NF-κB signaling pathway, disruption of intestinal flora, and disruption of intestinal tight junctions, according to several research findings [ 116 , 117 , 118 ]. Similarly, AP-associated ALI is exacerbated by HMGB1, which promotes inflammation by triggering nuclear translocation of NF-κB and inflammasome formation [ 119 , 120 ]. SAP may cause myocardial injury, which is an uncommon yet life-threatening consequence.…”
Section: Exosome-specific Proteinsmentioning
confidence: 99%